2013
DOI: 10.1093/molbev/mst092
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of 47 Chloroplast Genomes Clarifies the Contribution of Wild Species to the Domesticated Apple Maternal Line

Abstract: Both the origin of domesticated apple and the overall phylogeny of the genus Malus are still not completely resolved. Having this as a target, we built a 134,553-position-long alignment including two previously published chloroplast DNAs (cpDNAs) and 45 de novo sequenced, fully colinear chloroplast genomes from cultivated apple varieties and wild apple species. The data produced are free from compositional heterogeneity and from substitutional saturation, which can adversely affect phylogeny reconstruction. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 43 publications
11
80
1
Order By: Relevance
“…The results from Coart et al (2006) are in line with those recently reported based on the analysis of a dataset including 46 completely or nearly completely sequenced chloroplast genomes sampled across the genus Malus (Nikiforova et al 2013): the latter study indicated that M. sylvestris contributed the chloroplast genome to the majority of M. × domestica cultivars they examined. Note, however, that the domesticated apple probably did not arise from a single event over a short period of time, but from evolution extending over thousands of years.…”
Section: Chloroplast Dna Polymorphismsupporting
confidence: 82%
“…The results from Coart et al (2006) are in line with those recently reported based on the analysis of a dataset including 46 completely or nearly completely sequenced chloroplast genomes sampled across the genus Malus (Nikiforova et al 2013): the latter study indicated that M. sylvestris contributed the chloroplast genome to the majority of M. × domestica cultivars they examined. Note, however, that the domesticated apple probably did not arise from a single event over a short period of time, but from evolution extending over thousands of years.…”
Section: Chloroplast Dna Polymorphismsupporting
confidence: 82%
“…There are examples of where whole chloroplast sequences have been used to measure phylogeny and estimate divergence times of closely related species. This was utilized previously [49], where chloroplast genomes from 47 apple taxa were used, including both wild and domesticated taxa. By using the whole chloroplast sequence, a complete phylogeny and estimates of divergence times of the taxa could be obtained [49].…”
Section: Discussionmentioning
confidence: 99%
“…sikkimensis and M. spectabilis were not included in the phylogenetic analyses of SbeI gene sequences due to a lack of samples. Nonetheless, M. sieboldii could be used as a representative of the maternal lineage as phylogenetic analysis of Malus chloroplast genomes indicated a relatively close affinity among M. sieboldii , M. sikkimensis , and M. spectabilis (Nikiforova et al, ). The S1‐type SbeI sequences identified in M. sieboldii and M. toringoides belong to a well‐supported clade (clade I in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chloroplast haplotypes of M. transitoria , M. kansuensis , and M. toringoides as well as the three new hybrids were inferred from the chloroplast sequences generated in this study; chloroplast haplotypes of other Malus species were inferred based on the chloroplast sequences retrieved from Nikiforova et al ().…”
Section: Methodsmentioning
confidence: 96%